DEVELOPMENT OF STUDENTS’ INNOVATIVE COMPETENCES IN THE ACADEMIC ENVIRONMENT: DETERMINANTS AND CAREER PATHS - Matejun, Marek (PEOPLE: International Journal of Social Sciences, 2017)
The aim of the paper is to assess the level and determine the factors of development of students’ innovative competences in the academic environment of a selected university in Poland, as well as to identify the main directions of students’ planned career paths. This aim is realized on the basis of the research carried out in the framework of the 2nd Edition of the international research project Global University Entrepreneurial Spirit Students’ Survey (GUESSS) on a sample of 1,597 students of Lodz University of Technology, Poland. There were 3 research questions posed. The results indicate that the level of innovative competences is significantly and positively influenced by the level of entrepreneurship classes and the support on the part of university friends for entrepreneurial and innovative initiatives undertaken. People with the highest level of these competences often have much more definite professional plans. More than half of them plan to implement their innovative ideas in their own companies, established after gaining experience as employees of small, medium-sized and large enterprises.